Kualitas Argumentasi Ilmiah Siswa Melalui Penerapan Problem Based Learning Dengan Pendekatan Flipped Classroom - Mentari Darma Putri; Nur Azizah Lubis; Tariza Fairuz (Postgraduate, University of Mataram, 2023)
This research is quantitative research with a descriptive method that aims to analyze and compare the quality of students' scientific arguments in experimental class 1 which is applied by the PBL model through Flipped Classroom approach with experimental class 2 which applies the PBL model only. Instruments to measure students' scientific argumentation skills are essay questions. The quality of the students' arguments was analyzed based on the completeness of the components and the strength of the arguments. Analysis of the completeness of students' argumentation components aims to determine the level of students' argumentation which consists of 5 levels. The strength of the students' arguments was analyzed and categorized into three categories, namely weak, moderately strong, and strong. The results showed that students' scientific argumentation skills based on the completeness of the argument components in both classes experienced a significant increase. Most of the students in both classes have level 3 argumentation skills, meaning that students can make claims accompanied by complete supporting grounds. Based on the analysis of students' argument strength, experimental class 1 showed better argument quality than experimental class 2 where the percentage of students with strong argument strength in experimental class 1 was higher. Therefore, it can be concluded that the application of PBL with Flipped Classroom approach can improve the quality of students' scientific arguments